Postmoderne refleksije prostora in časa - Kos, Drago (Družboslovne razprave, 2018)
The assumption that the erosion of spatial determinism increases the possibilities for the non-instrumental perception and use of space is central to the emergence of postmodern spatial arrangements and identities. The weakening of spatial determinism accelerates the imaginative "constructivity" of space. The new spatial cognitive-emotional constructions in the new relaxed circumstances enable variability in implementation of identity practices. At different spatial levels, we can expect attempts to establish new meanings. However, optimistic theoretical assumptions have lately been more and more likely to collide with the empirical limits of the postmodern systems' openness, which is already approaching dangerous traditionalist regressions. The question of whether the assumptions about a flexible non-confrontational response are in fact a pre/optimistic ideological construction is the fundamental motive of this text, which we try to answer using the Braudelian "rules of a new history".
Keywords: Postmodernism; Postmodernizem; prostor; Prostorska sociologija; Spatial sociology; Urban development; Urbani razvoj